-
Notifications
You must be signed in to change notification settings - Fork 5
/
Copy pathsumExtraScript.sml
426 lines (349 loc) · 12.5 KB
/
sumExtraScript.sml
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
311
312
313
314
315
316
317
318
319
320
321
322
323
324
325
326
327
328
329
330
331
332
333
334
335
336
337
338
339
340
341
342
343
344
345
346
347
348
349
350
351
352
353
354
355
356
357
358
359
360
361
362
363
364
365
366
367
368
369
370
371
372
373
374
375
376
377
378
379
380
381
382
383
384
385
386
387
388
389
390
391
392
393
394
395
396
397
398
399
400
401
402
403
404
405
406
407
408
409
410
411
412
413
414
415
416
417
418
419
420
421
422
423
424
425
426
open hardwarePreamble;
open alistTheory;
open monadsyntax;
val _ = new_theory "sumExtra";
(* Error type, should probably have a lot more cases *)
Datatype:
error = UnknownVariable
| TypeError
| TypeErrorMsg string
| InvalidIndex
| NotImplemented
| InvalidArgument
| CombError string
| CycleError
| InvalidProgram
| Impossible
End
val sum_bind_def = Define `
(sum_bind (INL l) _ = INL l) /\
(sum_bind (INR r) f = f r)`;
declare_monad ("sum", { bind = ``sum_bind``,
ignorebind = NONE,
unit = ``INR``,
guard = NONE,
choice = NONE,
fail = SOME ``INL`` });
enable_monadsyntax ();
enable_monad "sum";
Theorem sum_bind_INR:
!x f v. sum_bind x f = INR v <=> ?v'. x = INR v' /\ f v' = INR v
Proof
Cases \\ simp [sum_bind_def]
QED
Theorem sum_bind_cong:
∀x1 f1 f2. (∀x. f1 x = f2 x) ⇒ sum_bind x1 f1 = sum_bind x1 f2
Proof
rw [GSYM FUN_EQ_THM]
QED
Theorem sum_bind_id[simp]:
(∀x. sum_bind x INR = x) ∧ (∀x. sum_bind x (λx. INR x) = x)
Proof
simp [PULL_FORALL] \\ rpt Cases \\ simp [sum_bind_def]
QED
val sum_bind_INR_old = Q.store_thm("sum_bind_INR_old",
`!s f v. sum_bind s f = INR v ==> ?v'. s = INR v'`,
rw [sum_bind_INR]);
val sum_check_def = Define `
sum_check b err = if b then INR () else INL err`;
Theorem sum_check_INR:
!b err. sum_check b err = INR () <=> b
Proof
rw [sum_check_def]
QED
(* There's also a "map" in sumTheory, called ++ I think, but it takes two functions *)
val sum_map_def = Define `
(sum_map f (INR r) = INR (f r)) /\
(sum_map _ (INL v) = INL v)`;
val sum_map_INR = Q.store_thm("sum_map_INR",
`!x f v. sum_map f x = INR v <=> ?v'. x = INR v' /\ f v' = v`,
Cases \\ simp [sum_map_def]);
val sum_map_INR_old = Q.store_thm("sum_map_INR_old",
`!s f v. sum_map f s = INR v ==> ?v'. s = INR v'`,
rw [sum_map_INR]);
Theorem sum_map_cong:
∀x1 x2 f1 f2. (∀x. f1 x = f2 x) ∧ x1 = x2 ⇒ sum_map f1 x1 = sum_map f2 x2
Proof
rw [GSYM FUN_EQ_THM]
QED
val sum_for_def = Define `
sum_for s f = sum_map f s`;
val sum_for_INR = Q.store_thm("sum_for_INR",
`!s f v. sum_for s f = INR v <=> ?v'. s = INR v' /\ f v' = v`,
rw [sum_for_def, sum_map_INR]);
val sum_for_INR_old = Q.store_thm("sum_for_INR_old",
`!s f v. sum_for s f = INR v ==> ?v'. s = INR v'`,
rw [sum_for_INR]);
val sum_alookup_def = Define `
sum_alookup env var =
case ALOOKUP env var of
NONE => INL UnknownVariable
| SOME t => INR t`;
Theorem sum_alookup_INR:
!env k v. sum_alookup env k = INR v <=> ALOOKUP env k = SOME v
Proof
rw [sum_alookup_def] \\ TOP_CASE_TAC
QED
Theorem sum_alookup_INL:
!env k e. sum_alookup env k = INL e <=> ALOOKUP env k = NONE ∧ e = UnknownVariable
Proof
rw [sum_alookup_def] \\ TOP_CASE_TAC \\ simp []
QED
Theorem sum_alookup_nil[simp]:
!k. sum_alookup [] k = INL UnknownVariable
Proof
rw [sum_alookup_def]
QED
Theorem sum_alookup_cons:
!k1 k2 v env. sum_alookup ((k1, v)::env) k2 = if k1 = k2 then INR v else sum_alookup env k2
Proof
rw [sum_alookup_def]
QED
Theorem sum_alookup_append:
!var env1 env2.
sum_alookup (env1 ++ env2) var =
case sum_alookup env1 var of
INL e => sum_alookup env2 var
| INR v => INR v
Proof
rw [sum_alookup_def, ALOOKUP_APPEND] \\ every_case_tac \\ simp []
QED
(* mapM for sum: mapM :: Monad m => (a -> m b) -> t a -> m (t b) *)
(* TODO: The middle can be replaced by a sum_bind *)
val sum_mapM_def = Define `
(sum_mapM _ [] = INR []) /\
(sum_mapM f (x::xs) = case (f x) of
| INL l => INL l
| INR r => sum_map (CONS r) (sum_mapM f xs))`;
(* For proving termination *)
val sum_mapM_cong = Q.store_thm("sum_mapM_cong",
`!l1 l2 f f'. (l1 = l2) /\ (!x. MEM x l2 ==> (f x = f' x)) ==> (sum_mapM f l1 = sum_mapM f' l2)`,
Induct \\ rw [sum_mapM_def] \\ rw [sum_mapM_def] \\ TOP_CASE_TAC \\ match_mp_tac f_equals2 \\ rw []);
(* DefnBase.add_cong sum_mapM_cong; *)
DefnBase.export_cong "sum_mapM_cong";
Theorem sum_mapM_INR:
(!f v. sum_mapM f [] = INR v <=> v = []) ∧
(!f x xs v. sum_mapM f (x::xs) = INR v <=> ?x' xs'. f x = INR x' /\ sum_mapM f xs = INR xs' /\ v = x'::xs')
Proof
rw [sum_mapM_def] \\ CASE_TAC \\ simp [sum_map_INR] \\ metis_tac []
QED
Theorem length_sum_mapM:
∀l l' f. sum_mapM f l = INR l' ⇒ LENGTH l' = LENGTH l
Proof
Induct >- rw [sum_mapM_def] \\ rw [sum_mapM_INR] \\ drule_first \\ simp []
QED
Theorem sum_mapM_append:
!l1 l2 l3 f.
sum_mapM f (l1 ++ l2) = INR l3 <=> ?l1' l2'. sum_mapM f l1 = INR l1' /\ sum_mapM f l2 = INR l2' ∧ l3 = l1' ++ l2'
Proof
Induct >- rw [sum_mapM_def] \\ rw [sum_mapM_INR] \\ eq_tac \\ rw [PULL_EXISTS]
QED
Theorem sum_mapM_EL:
∀l l' f. sum_mapM f l = INR l' ⇔ (LENGTH l' = LENGTH l ∧ ∀i. i < LENGTH l ⇒ f (EL i l) = INR (EL i l'))
Proof
Induct \\ rw [sum_mapM_INR] \\ eq_tac
>- (rpt strip_tac \\ fs [] \\ Cases_on ‘i’ \\ fs [])
\\ rpt strip_tac \\ Cases_on ‘l'’ \\ fs [] \\ rw []
>- (first_x_assum (qspec_then ‘0’ mp_tac) \\ simp [])
\\ first_x_assum (qspec_then ‘SUC i’ mp_tac) \\ simp []
QED
Theorem sum_mapM_MEM:
∀l l' f x. sum_mapM f l = INR l' ∧ MEM x l' ⇒ ∃y. f y = INR x ∧ MEM y l
Proof
simp [sum_mapM_EL, MEM_EL] \\ metis_tac []
QED
Theorem sum_mapM_EVERY:
!l l' f. sum_mapM f l = INR l' ==> EVERY (\e. ∃x. f e = INR x) l
Proof
Induct \\ rw [sum_mapM_INR] \\ metis_tac []
QED
val sum_mapM__def = Define `
(sum_mapM_ _ [] = INR ()) /\
(sum_mapM_ f (x::xs) =
case f x of
INL l => INL l
| INR r => sum_mapM_ f xs)`;
Theorem sum_mapM__INR:
!f x xs v. sum_mapM_ f (x::xs) = INR v <=> ?v'. f x = INR v' /\ sum_mapM_ f xs = INR v
Proof
rw [sum_mapM__def] \\ CASE_TAC
QED
Theorem sum_mapM__EVERY:
!ps f. sum_mapM_ f ps = INR () ==> EVERY (\p. f p = INR ()) ps
Proof
Induct \\ rw [sum_mapM__INR]
QED
(* TODO: Might be useful *)
(*val sum_filterM_def = Define `
(sum_filterM P [] = return []) /\
(sum_filterM P (x::xs) = do
xs' <- sum_filterM P xs;
return (if P x then xs' else x :: xs)
od)`;*)
(* listTheory.MAP2 for sums *)
(*val sum_map2M_def = Define `
(sum_map2M _ [] [] = INR []) /\
(sum_map2M f (x::xs) (y::ys) = sum_bind (f x y) (\xy. sum_map (CONS xy) (sum_map2M f xs ys)))`;*)
(* Monomorphic liftM2 *)
val sum_liftM2_def = Define `
sum_liftM2 f mx my = sum_bind mx (\x. sum_bind my (\y. INR (f x y)))`;
val sum_liftMM2_def = Define `
sum_liftMM2 f mx my = sum_bind mx (\x. sum_bind my (\y. f x y))`;
(*
val sum_liftM3_def = Define `
sum_liftM3 f mx my mz = sum_bind mx (\x. sum_bind my (\y. sum_bind mz (\z. INR (f x y z))))`;
*)
val sum_foldM_def = Define `
(sum_foldM f z [] = INR z) /\
(sum_foldM f z (x::xs) = sum_bind (f z x) (\fx. sum_foldM f fx xs))`;
Theorem sum_foldM_INR:
(!acc f. sum_foldM f acc [] = INR acc) ∧
(!x xs acc f v. sum_foldM f acc (x::xs) = INR v <=> ?v'. f acc x = INR v' /\ sum_foldM f v' xs = INR v)
Proof
rw [sum_foldM_def, sum_bind_INR]
QED
Theorem sum_foldM_append:
!xs ys i f. sum_foldM f i (xs ++ ys) = sum_bind (sum_foldM f i xs) (\i. sum_foldM f i ys)
Proof
Induct \\ rw [sum_foldM_def, sum_bind_def] \\ Cases_on `f i h` \\ rw [sum_bind_def]
QED
Theorem sum_foldM_SNOC:
!xs x y f. sum_foldM f y (SNOC x xs) = sum_bind (sum_foldM f y xs) (combin$C f x)
Proof
rw [SNOC_APPEND, sum_foldM_append, sum_foldM_def] \\
Cases_on `sum_foldM f y xs` \\ rw [sum_bind_def, sum_bind_id, ETA_THM]
QED
Theorem sum_foldM_cong:
∀l l' b b' f f'.
l = l' ∧ b = b' ∧ (∀x a. MEM x l' ⇒ f a x = f' a x) ⇒
sum_foldM f b l = sum_foldM f' b' l'
Proof
Induct >- simp [sum_foldM_def] \\ Cases_on ‘l'’ \\ rw [sum_foldM_def] \\
f_equals_tac \\ rw [FUN_EQ_THM]
QED
DefnBase.export_cong "sum_foldM_cong";
(* Name from arithmeticTheory.FUNPOW *)
val sum_funpowM = Define `
(sum_funpowM f 0 x = INR x) /\
(sum_funpowM f (SUC n) x = sum_bind (f x) (\fx. sum_funpowM f n fx))`;
val sum_option_map_def = Define ‘
(sum_option_map f (SOME x) = sum_map SOME (f x)) /\
(sum_option_map f NONE = return NONE)’;
Theorem sum_option_map_INR:
!f x x'.
sum_option_map f x = INR x' <=> (x = NONE /\ x' = NONE) \/ (?y y'. x = SOME y /\ x' = SOME y' /\ f y = INR y')
Proof
Cases_on ‘x’ \\ rw [sum_option_map_def, sum_map_INR] \\ metis_tac []
QED
Theorem sum_option_map_cong:
!o1 o2 f1 f2. (o1 = o2) ∧ (∀x. o1 = SOME x ⇒ f1 x = f2 x) ⇒ sum_option_map f1 o1 = sum_option_map f2 o2
Proof
Cases \\ simp [sum_option_map_def]
QED
DefnBase.export_cong "sum_option_map_cong";
(* Same as listTheory.EL but returns sum monad on out of bounds *)
val sum_EL_def = Define `
(sum_EL _ [] = INL InvalidIndex) /\
(sum_EL 0 (h::t) = INR h) /\
(sum_EL (SUC i) (_::t) = sum_EL i t)`;
(* Cleanup? *)
val sum_EL_INR_EL = Q.store_thm("sum_EL_INR_EL",
`!i l e. EL i l = e /\ i < LENGTH l ==> sum_EL i l = INR e`,
Induct \\ rpt strip_tac
>- (Cases_on `l` \\ fs [sum_EL_def])
\\ Cases_on `i = LENGTH l` >- fs [] \\
`i < LENGTH l` by DECIDE_TAC \\ Cases_on `l` >- fs [] \\
fs [sum_EL_def]);
val sum_EL_INR_EL2 = Q.store_thm("sum_EL_INR_EL2",
`!i l. i < LENGTH l ==> sum_EL i l = INR (EL i l)`,
metis_tac [sum_EL_INR_EL]);
(* Same as sum_EL, but in reverse *)
val sum_revEL_def = Define `
sum_revEL i vs = let l = LENGTH vs in
if i < l
then sum_EL (l - 1 - i) vs
else INL InvalidIndex`;
(** Some simpl thms about the sum type **)
Theorem sum_EL_INR:
!l e i. sum_EL i l = INR e <=> e = EL i l /\ i < LENGTH l
Proof
Induct >- rw [sum_EL_def] \\ Cases_on ‘i’ \\ rw [sum_EL_def] \\ metis_tac []
QED
Theorem sum_EL_EL:
!i l. i < LENGTH l ==> sum_EL i l = INR (EL i l)
Proof
rw [sum_EL_INR]
QED
val sum_EL_eq_EL = Q.store_thm("sum_EL_eq_EL",
`!i l e. i < LENGTH l ==> (sum_EL i l = INR e <=> EL i l = e)`,
Induct \\ rpt strip_tac \\ Cases_on `l` \\ fs [sum_EL_def]);
val sum_EL_LENGTH = Q.store_thm("sum_EL_LENGTH",
`!xs x y. sum_EL (LENGTH xs) (xs ++ [x]) = INR x`,
Induct \\ rw [sum_EL_def]);
(*
val sum_revEL_0 = Q.store_thm("sum_revEL_0",
`!xs x y. sum_revEL 0 (xs ++ [x]) = INR y ==> x = y`,
rw [sum_revEL_def, sum_EL_def] \\ metis_tac [sum_EL_LENGTH]);
*)
val sum_EL_LENGTH_INR_LENGTH = Q.store_thm("sum_EL_LENGTH_INR_LENGTH",
`!n xs x y. n < LENGTH xs /\ sum_EL (LENGTH xs − n) (x::xs) = INR y ==>
sum_EL (LENGTH xs − (n + 1)) xs = INR y`,
rpt strip_tac \\ `LENGTH xs − (n + 1) = LENGTH xs − n - 1` by DECIDE_TAC \\
pop_assum (fn th => REWRITE_TAC [th]) \\
Cases_on `LENGTH xs − n` \\ fs [sum_EL_def]);
val sum_EL_APPEND_EQN = Q.store_thm("sum_EL_APPEND_EQN",
`!l1 l2 n.
sum_EL n (l1 ++ l2) = if n < LENGTH l1 then sum_EL n l1 else sum_EL (n − LENGTH l1) l2`,
Induct \\ rw [] \\ Cases_on `n` \\ fs [sum_EL_def]);
val sum_revEL_LENGTH = Q.store_thm("sum_revEL_LENGTH",
`!xs x. sum_revEL (LENGTH xs) (x::xs) = INR x`,
Induct \\ rw [sum_revEL_def, sum_EL_def]);
val sum_revEL_APPEND_EQN = Q.store_thm("sum_revEL_APPEND_EQN",
`!l2 l1 n.
sum_revEL n (l1 ++ l2) =
if n < LENGTH l2 then sum_revEL n l2 else sum_revEL (n − LENGTH l2) l1`,
rw [sum_revEL_def] \\ fs [sum_EL_APPEND_EQN]);
(*
val sum_revEL_APPEND_single = Q.store_thm("sum_revEL_APPEND_single",
`!n xs x. sum_revEL (SUC n) (xs ++ [x]) = sum_revEL n xs`,
rw [sum_revEL_def, sum_EL_APPEND_EQN, ADD1]);
*)
val sum_revEL_0 = Q.store_thm("sum_revEL_0",
`!xs x. sum_revEL 0 (xs ++ [x]) = INR x`,
Induct \\ rw [sum_revEL_def, sum_EL_def, sum_EL_LENGTH]);
Theorem sum_revEL_INR:
!l e i. sum_revEL i l = INR e <=> e = revEL i l /\ i < LENGTH l
Proof
rw [sum_revEL_def, revEL_def, sum_EL_INR]
QED
Theorem sum_revEL_revEL:
!l i. i < LENGTH l ==> sum_revEL i l = INR (revEL i l)
Proof
rw [sum_revEL_INR]
QED
val sum_revEL_INR_LENGTH = Q.store_thm("sum_revEL_INR_LENGTH",
`!n xs x y. n < LENGTH xs /\ sum_revEL n (x::xs) = INR y ==> sum_revEL n xs = INR y`,
rw [sum_revEL_def] \\ metis_tac [sum_EL_LENGTH_INR_LENGTH]);
val MEM_sum_revEL = Q.store_thm("MEM_sum_revEL",
`!l x. MEM x l <=> ∃n. n < LENGTH l /\ INR x = sum_revEL n l`,
Induct \\ rw [] \\ eq_tac \\ rw []
>- (qexists_tac `LENGTH l` \\ rw [sum_revEL_def, sum_EL_def])
>- (qexists_tac `n` \\ `h::l = [h] ++ l` by simp [] \\
pop_assum (fn th => rewrite_tac [th]) \\ rewrite_tac [sum_revEL_APPEND_EQN] \\
simp [])
\\ Cases_on `n = LENGTH l`
>- (rveq \\ fs [sum_revEL_LENGTH])
\\ `n < LENGTH l` by decide_tac \\ metis_tac [sum_revEL_INR_LENGTH]);
Theorem ISR_exists:
!x. ISR x <=> ?x'. x = INR x'
Proof
Cases \\ rw [sumTheory.ISR]
QED
(*Definition sum_everyM_def:
(sum_everyM P [] = INR T) ∧
(sum_everyM P (h::t) = do
Ph <- P h;
if Ph then sum_everyM P t else INR F
od)
End*)
val _ = export_theory ();